Jurnal Penyuluhan: Pengembangan Pertanian Organik di Kelompok Tani Madya, Desa Kebonagung, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Firda Emiria, Heru Purwandari (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
Organic farming is agricultural activities that seek the use of outside intake and avoid the use of pesticides and synthetic fertilizer. The results showed that the organic farmers and conventional farmers have the high responses of organic farming. However, the characteristics of organic farmer have no relation with farmer’s respons of organic farming.